Registration of a Laser Beam Scattered from an Aerosol Located in the Probe Beam Aperture; AIP Conference Proceedings; Vol. 2101 : Isotopes: Technologies, Materials and Application (ITMA-2018) - Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Khan V. A. Valery Alekseevich; Tichy M. Milan; Kapran A. Anna; Borisov V. A. Valentin; Gamov D. L. Denis Leonidovich; Zaguzin I. Ju. Ilya (2019, 2019)
Title screen